Pemberian Kompres Hangat Jahe Terhadap Menurunkan Nyeri Punggung pada Ibu Hamil Trimester III : Studi Kasus - Nova Yusenta; Septika Yani Veronica (Universitas Harapan Bangsa Purwokerto, 2023)
Pregnancy is the growth and development of the intrauterine fetus starting from conception and ending until the beginning of labor. During pregnancy, the mother will experience changes both physically and psychologically. Physical changes that occur sometimes even provide discomfort for the mother, one of which is lower back pain. One way to reduce low back pain is with ginger compresses, ginger compresses can reduce the low back pain they experience. Purpose Provide continuous obstetric care starting from pregnancy, childbirth, newborn, postpartum to contraceptive services with complementary interventions by giving warm compresses of ginger to reduce back pain in III trimester pregnant women. Methods used in comprehensive care Type of descriptive research using the case study approach method. There is a decrease in back pain in pregnant women after a warm compress of ginger. It is expected to use warm ginger compresses when experiencing back pain. Keywords : Pregnancy, Ginger Compress